Heart–brain interaction in cardiogenic dementia: pathophysiology and therapeutic potential - Liu, Jiaxu; Xiao, Guangxu; Liang, Yujuan; He, Shuang; Lyu, Ming; Zhu, Yan (Frontiers in Cardiovascular Medicine, 2024)
The diagnostics and treatment of patients with cardiovascular and neural diseases have primarily focused on heart and and brain, respectively. More and more preclinical and clinical studies have confirmed a causal relationship between the heart and brain diseases. In particular, cardiogenic dementia, a cognitive impairment caused by heart dysfunction, has received increased research attention. Prevention and treatment of cardiogenic dementia are essential to the improvement of the quality of life, particularly for the elderly and aging population. This article describes the changes in cognitive function associated with coronary artery disease, myocardial infarction, heart failure, atrial fibrillation and heart valve disease. Updated understanding on the two known pathogenic mechanisms of cardiogenic dementia, one being a cascade of events caused by cerebral hypoperfusion due to long-term reduction of cardiac output after heart disease and the other being cognitive impairment regardless of the changes in cerebral blood flow after cardiac injury, are presented and discussed. Furthermore, potential medications for the prevention and treatment of cardiogenic dementia are reviewed, with a special attention to multi-component herbal medicine.